Impact of Coronavirus Disease 2019 in Cesarean Delivery and Neonates: A Case-Control Study - Juseok Yang; Ji Eun Park; Jong Chul Baek; Iyun Kwon; Hyen Chul Jo (IMR Press, 2023)
Background: The aim of this study was to compare the maternal, surgical, and neonatal outcomes in pregnant women with coronavirus disease 2019 (COVID-19) who underwent cesarean delivery at term and provide evidence for the management of parturient with COVID-19. Methods: This case-control study was conducted retrospectively and evaluated 67 cases of cesarean delivery between February 1 and May 31 performed at the Gyeongsang National University Changwon Hospital, Korea. Case group included women who had positive reverse transcriptase-polymerase chain reaction (RT-PCR) test within 7 days before delivery. Control group was selected based on mode of delivery and gestational age among women with negative RT-PCR result. Results: A total of 34 women with COVID-19 and 33 COVID-19-negative women and their neonate were included in this study. Preoperative C-reactive protein was higher in case group (6.4 mg/L vs 1.8 mg/L, p < 0.001), but preoperative and postoperative day 1 and 3 hemoglobin levels did not differ between groups. Postoperative complications were similar in both groups. Control group had higher 1- and 5-minute APGAR scores than case group (p = 0.006 and p = 0.005) and showed better results of cord blood analyses in cord blood pH and base deficit (p = 0.001 and p = 0.002). Neonatal admission to intensive care unit did not differ between groups and there was no vertical transmission of COVID-19. Conclusions: Pregnant women with coronavirus disease 2019 at term who underwent urgent cesarean delivery showed comparable surgical and neonatal outcomes except higher preroperative C-reactive protein levels compared to COVID-19-negative women.